A UNIVERSITY QUALITY ASSURANCE TEAM SHOULD STRIVE FOR QUALITY OF WORK-LIFE - Dzikrina Syahidah; Siti Zulaikha; Masduki Ahmad (LPMPP Universitas Negeri Yogyakarta, 2021)
Professionalism is an important key to an organization in achieving their success. One of the essential factors influencing the formation of committed professional resources is the employees’ perception of the quality of their work life. This study aims to examine the effects of the quality of work life (QWL) (appropriate and fair compensation, work stress, employee participation, career growth and development, social relevance, work environment) on organizational commitment (OC) simultaneously or partially. The participants of this study were 109 quality assurance team employees at a state university in Indonesia. The data collected through questionnaires were analyzed by simple regression and Pearson’s correlation test. The results showed that there is a significant influence between QWL and OC. The six predictors of QWL showed a significant relationship with OC (r .05) with the most influencing indicators as follows: career growth and development (p = .612), appropriate and fair compensation (p = .558), employee participation (p = .515), work stress (p = ˗.510), social relevance (p = .498), and work environment (p = .422). This study suggests that a state university shoud provide wider opportunities for quality assurance employees to develop and demonstrate their abilities and creativity as an effort to increase their OC.